Stabilometry and body composition analysis in professional players from different sports - Moreno, R.; Mendizabal, S.; Ramos, D.; Rubio, J. A.; Jiménez, F. (Archivos de medicina del deporte, 2008)
Feet are some of the structures that further suffer the consequences of the practice of physical activity, for they receive directly impacts and absorb ground reaction forces. These conditions can produce signifi cant changes, specially in high-performance sports. The study of Plantar Pressures and Its relationship to other variables such as muscle-skeletal mass and the displacement of Centre of Pressure can contribute to prevent sport injuries. Materials and methods: 52 high-level athletes and 52 healthy subjects have been studied, with a measure of Body Composition by bioimpedance (Inbody720) and distribution of Plantar Pressures, with a pressure platform, as well as the displacement of the Centre of Pressure (Footwork-Pro). The aim of this study was to observe the relationship between Plantar Pressures distribution, muscle-skeletal mass and displacement of Centre of Pressure in (three) different populations. Results: We found significant difference p<0.05 in MME among healthy subjects and handball, basketball and rugby. (Group handball = 50.25 kg; Group basketball = 49.4 kg; Group rugby = 46.03 kg Group Healthy Subjects= 32.07 kg). In MGC there are signifi cant differences between rugby players and active participants. (Group rugby = 16.6 kg group and healthy subjects = 12.31 kg). Mean PP Left show signifi cant differences exist among active players and handball and rugby (Group healthy subjects = 8.74 kg/cm2; rugby Group = 11.74 kg/ cm2; Group handball kg/cm2 = 13.02). Furthermore the Mean PP Right kg/cm2 have also signifi cant differences among healthy subjects and rugby and handball (Group Healthy Subjects = 8.78 kg/cm2; rugby Group = 11.81 kg/cm2; Group handball = 13.01 kg/cm2). In the Left COP exist signifi cant differences between the healthy subjects and basketball players from rugby, handball and active, but not in Right COP. (Group active = 1.08 cm2; rugby Group = 0.59 cm2; Group handball = 1.30 cm2). Body COP, there show signifi cant differences between rugby players and active participants. Group active = 3.51 cm2 and rugby Group = 1.69 cm2). Conclusions: High performance sport class influences body composition changes of the sample studied. Body composition does not infl uence in a signifi cant way in the centre of pressure displacement of the professional player of this study. Training isn`t a key factor to alter stabilometric parameters with regard to the healthy subjects of this study.